Relationship Between SEM Training (Smart Entrepreneur Model) With Attitude PMW Participant Students in Running Business - Rizka Darmawan; Alim Harun Pamungkas (Universitas Negeri Padang, 2021)
This research is motivated by the low attitude of the students participating in the PMW (Student Entrepreneurial Program) in running a business, this is presumably because it has something to do with the SEM (Smart Entrepreneur Model) training held by UPKK UNP properly. This study aims to: 1) describe the implementation of SEM (Smart Entrepreneur Model) training; 2) describe the attitudes of PMW participants in running a business; and 3) see the relationship between the Smart Entrepreneur Model Training and the attitudes of PMW participants in running a business. This type of research is quantitative research with correlational descriptive technique. The population of this study were all participants of the Smart Entrepreneur Model training, totaling 85 students. While the research population was 43 students who were taken using simple random sampling technique. Data collection techniques in the form of a Likert scale with data collection tools in the form of a questionnaire. The data analysis technique uses the percentage formula and product-moment correlation. The results showed that: (1) The implementation of the SEM (Smart Entrepreneur Model) training had not been carried out properly, (2) The attitude of the PMW participant students in running a business was relatively low, (3) There was a significant relationship between the SEM (Smart Entrepreneur Model) training and the attitude of PMW participants in running a business. It is recommended to UPKK UNP as the organizer of the SEM (Smart Entrepreneur Model) Training to improve and further improve the implementation of the training to improve students' abilities in entrepreneurship and to PMW participating students to be more active in participating in training so that knowledge and knowledge in entrepreneurship will increase.